2018
DOI: 10.1029/2017tc004935
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Distributed Faulting During the 30 October 2016, Central Italy Earthquake: A Reference for Fault Displacement Hazard Assessment

Abstract: Moderate to strong earthquakes (i.e., Mw >~6.0) commonly produce a complex network of ground ruptures, which are responsible for significant damage. Distributed faulting can affect wide areas (tenths of square kilometers), and expected displacement can be estimated through a probabilistic approach, considering distance from the primary fault and earthquake magnitude. Other factors may have a role in driving the occurrence of distributed faulting; nevertheless, they are not adequately addressed in the current m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Several geologic surveys resulted in (1) a surface rupture map, drawn by inspecting a selection of ~11,000 oblique‐view photos from helicopter flights, verified and integrated with field data (Civico et al, ), and (2) an open‐access database of surface coseismic effects (Villani et al, ). Ferrario and Livio () focus on the role of lithology and structural setting in the pattern of surface faulting. Wilkinson et al (), by using low‐cost GPS units located in the footwall and in the hanging wall of some splays of the VBFS, demonstrate that the surface rupture process completed within 6–8 s from the origin time of the mainshock, before the onset of the peak ground acceleration: therefore, they infer that the coseismic surface breaks developed at a rate comparable to the rupture propagation speed, as direct expression of primary surface faulting.…”
Section: Geological Background and Seismotectonic Frameworkmentioning
confidence: 99%
“…Several geologic surveys resulted in (1) a surface rupture map, drawn by inspecting a selection of ~11,000 oblique‐view photos from helicopter flights, verified and integrated with field data (Civico et al, ), and (2) an open‐access database of surface coseismic effects (Villani et al, ). Ferrario and Livio () focus on the role of lithology and structural setting in the pattern of surface faulting. Wilkinson et al (), by using low‐cost GPS units located in the footwall and in the hanging wall of some splays of the VBFS, demonstrate that the surface rupture process completed within 6–8 s from the origin time of the mainshock, before the onset of the peak ground acceleration: therefore, they infer that the coseismic surface breaks developed at a rate comparable to the rupture propagation speed, as direct expression of primary surface faulting.…”
Section: Geological Background and Seismotectonic Frameworkmentioning
confidence: 99%
“…It is unclear because on the 30 October 2016, before field surveys of the 26 October earthquakes, a M w 6.5 earthquake ruptured the total length of the Mt. Vettore fault, rerupturing locations that slipped in the 24 August 2016 earthquake and perhaps those on the 26 October (see Figures , , and ; Calderoni et al, ; Cheloni et al, ; Chiaraluce et al, ; Civico et al, ; Falcucci et al, ; Ferrario & Livio, ; Lavecchia et al, ; Mildon et al, ; Pavlides et al, ; Perouse et al, ; Pizzi et al, ; Porreca et al, ; Scognamiglio et al, ; Verdecchia et al, ; Villani, Civico, et al, ; Villani, Pucci, et al, ; Walters et al, ). Meter‐scale offset across surface ruptures was measured with near‐field 1‐Hz global navigation satellite system for the 30 October ruptures, revealing that the ruptures formed within 2–4 s and, before peak ground acceleration, supporting the primary tectonic origin of the ruptures (Wilkinson et al, ; Figure ).…”
Section: Geologic Backgroundmentioning
confidence: 99%
“…Today, plentiful seismological, geodetical, geological, and macroseismic papers (Cheloni et al, ; Chiaraluce et al, ; Ferrario & Livio, ; Galli, Castenetto, & Peronace, ; Pizzi et al, ; Scognamiglio et al, ; Villani et al, ) have demonstrated that the MVFS is undoubtedly the seismogenic structure responsible for the seismic sequence started on 24 August 2016. The entire MVFS ruptured at surface for a length of ~30 km on 30 October, reactivating the surface breaks formed along the southern and northern tips on 24 August and 26 October, respectively (Civico et al, ).…”
Section: Introductionmentioning
confidence: 99%